Prenatal opioid exposure alters pain perception and increases long-term health risks in infants with neonatal opioid withdrawal syndrome - Radhakrishna, Uppala; Radhakrishnan, Rupa; Uppala, Lavanya V.; Trivedi, Tithi S.; Prajapati, Jignesh; Rawal, Rakesh M.; Muvvala, Srinivas B.; Bahado-Singh, Ray O.; Sadhasivam, Senthilkumar (Frontiers in Pain Research, 2025)
BackgroundOpioids are often prescribed for pain relief, yet they pose risks such as addiction, dependence, and overdose. Pregnant women have unique vulnerabilities to opioids and infants born to opioid-exposed mothers could develop neonatal opioid withdrawal syndrome (NOWS). The study of opioid-induced epigenetic changes in chronic pain is in its early stages. This study aimed to identify epigenetic changes in genes associated with chronic pain resulting from maternal opioid exposure during pregnancy.MethodsWe analyzed DNA methylation of chronic pain-related genes in 96 placental tissues using Illumina Infinium Methylation EPIC BeadChips. These samples comprised 32 from mothers with infants prenatally exposed to opioids who needed pharmacologic NOWS management (+Opioids/+NOWS), 32 from mothers with prenatally opioid-exposed infants not needing NOWS pharmacologic treatment (+Opioids/-NOWS), and 32 from unexposed control subjects (-Opioids/-NOWS).ResultsThe study identified significant methylation changes at 111 CpG sites in pain-related genes among opioid-exposed infants, with 54 CpGs hypomethylated and 57 hypermethylated. These genes play a crucial role in various biological processes, including telomere length regulation (NOS3, ESR1, ESR2, MAPK3); inflammation (TNF, MAPK3, IL1B, IL23R); glucose metabolism (EIF2AK3, CACNA1H, NOTCH3, GJA1); ion channel function (CACNA1C, CACNA1H, CLIC4, KCNQ5); autophagy (CTSS, ULK1, ULK4, ATG5); oxidative stress (NGF, NRG1, OPRM1, ATP1A2); aging (GRIA1, NGFR, PRLR, EIF4E); cytokine activity (TRPV4, RUNX1, CXCL8, IL18R1); and the risk of suicide (ADORA2A, ANKK1, GABRG2, IGSF9B). These epigenetic changes may influence 48 signaling pathways—including cAMP, MAPK, GnRH secretion, estrogen signaling, morphine addiction, circadian rhythms, and insulin secretion—profoundly affecting pain and inflammation-related processes.ConclusionThe identified methylation alterations may shed light on pain, neurodevelopmental changes, and other biological mechanisms in opioid-exposed infants and mothers with OUD, offering insights into NOWS and maternal-infant health. These findings may also pave the way for targeted interventions and improved pain management, highlighting the potential for integrated care strategies to address the interconnected health of mothers and infants.